Spatio-temporal distribution and habitat preference of necrophagous Calliphoridae based on 160 real cases from Switzerland - Hodecek, Jiri; Jakubec, Pavel (International journal of legal medicine, 2022)
Necrophagous blowflies (Diptera: Calliphoridae) are of great importance particularly during investigations of suspicious deaths. Many studies have analyzed the distribution of blowflies based on pig experiments and baited trapping; however, data from real case scenarios are rarely used. In this article, the distribution of blowflies found during investigations of 160 real cases during 1993-2007 in Switzerland is evaluated based on habitat, altitude, and season. Ten species of blowflies were present in 145 out of the 160 cases. The most common species was Calliphora vicina, which occurs throughout the year and was present in 69 % of all cases. Lucilia sericata, Calliphora vomitoria, and L. caesar were identified among the rest of the flies as species of great forensic importance mainly due to their distributional patterns. After a comparison with a similar dataset from Frankfurt, Germany, some surprising differences were determined and discussed. The biggest discrepancies between our dataset and the German dataset were in the occurrences of L. sericata (30 % vs. 86 %, respectively), Phormia regina (5 % vs. 43 %), and L. ampullacea (1 % vs. 45 %). The life-history strategies and intraspecific behavioral variability of blowflies remain understudied, although they can be essential for an unbiased approach during a death investigation. Further research and comparison of occurrence patterns across the area of distribution of blowflies are therefore needed and recommended.
Keywords: Blowflies; Animals; Humans; Investigation; Forensic entomology; lidé; Altitude; Diptera; Calliphoridae; Real cases; Švýcarsko; Switzerland; zvířata; ekosystém; Ecosystem